Grief-induced reversible cerebral vasoconstriction syndrome (RCVS). Issue 1 (29th January 2020) - Rao, Pooja; McCullough, Michael Francis; Stevens, Jessica; Edwardson, Matthew A
Abstract : Stress is under-recognised as a potential causative factor for reversible cerebral vasoconstriction syndrome (RCVS). Here we present a case of RCVS occurring during a time of extreme emotional duress. A 46-year-old female patient with medical history of bipolar disorder developed a severe headache during her father's funeral. The following day she was discovered to have bilateral hemiparesis, aphasia, encephalopathy and was brought emergently to the hospital. Neuroimaging revealed a 33 mL left fronto-parietal haematoma with subarachnoid blood near the vertex bilaterally. She underwent craniotomy, haematoma evacuation and external ventricular drain placement. The patient received two cerebral angiograms, the first showing multifocal cerebral vasoconstriction and the second showing resolution of these changes. She improved significantly over the course of her 3-week hospitalisation and eventually made a full recovery, including the ability to speak fluently in six languages with no significant deficits other than hypersomnia; she now requires 10 hours of sleep each night as compared with 7 hours prior to her brain injury.